Struktur Komunitas Dan Preferensi Habitat Makrozoobentos Pada Kondisi Padang Lamun Yang Berbeda Di Kawasan Pantai Sanur Bali - Ketut Popi Anjani Devi; I Gusti Sila Dharma; I Nyoman Giri Putra (Department of Marine Sciences, Faculty of Marine Science and Fisheries, Udayana University, 2019)
The existence of macrozoobenthos in habitats is strongly influenced by physical and chemical conditions of water. One of the macrozoobenthos habitats is seagrass, the amount of seagrass cover and organic matter greatly influences the structure of the macrozoobenthos community. Seagrass in the Sanur Beach area grows on an 8 km stretch of beach stretching from Grand Bali Beach Hotel to Mertasari. In the Sanur Beach area, a lot of research refers to the association of macrozoobenthos in seagrasses and a description of the distribution of mollusca. This study aims to determine the macrozoobenthos community structure. This research was conducted in the Sanur beach area, namely at Segara Ayu Beach and Semawang Beach. In this study macrozoobenthos data collection was carried out by substrate retrieval, and aquatic environmental parameters. The highest species composition at the two stations came from the Cycloneritida sequence, the individual abundance at Segara Ayu beach was higher than Semawang Beach which was 0.024 ind/m3, this was thought to be due to higher seagrass density at Segara Ayu Beach than at Semawang Beach. Diversity index in both stations was classified as medium, high uniformity index, and low dominance index.